Keselamatan Sebagai Ketentuan Allah Semata (Monergisme) VS Keselamatan Hasil Kontribusi Manusia (Sinergisme):Analisis Teologi Paulus - Clara Silambi; Christin Meli Sartika; Emilisa Ponda (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
This journal was written with the aim of discussing Paul's theology of God's salvation, monergism and synergism. Reviewing Paul's theology of God's true salvation will lead people to a fundamental understanding and strengthen one's hold on being a Christian. There is an understanding that salvation is a human effort and God's work (Synerism). Basically, salvation is the work of God in freeing man from sin. For by the grace of God salvation is wrought, that is, by the sacrifice and redemption of His Only Begotten Son, Jesus Christ. So through this writing, man must hold fast that salvation is a gift from God, not a human effort. This writing method uses a qualitative method through library search, through text sources, such as academic journals, books, papers, and other related literature available in the library.